Hepatitis C in Sub-Saharan Africa: Urgent Need for Attention. (17th September 2014) - Layden, Jennifer E.; Phillips, Richard; Opare-Sem, Ohene; Akere, Adegboyega; Salako, Babatunde L.; Nelson, Kenrad; Dugas, Lara; Luke, Amy; Tayo, Bamidele O.; Cooper, Richard S.
Abstract: The hepatitis C virus (HCV), which was not recognized as an infectious agent until the 1980s, is responsible for a worldwide epidemic. The World Health Organization estimates global prevalence at 2.8%, with 185 million persons infected. In contrast to hepatitis B, where successful vaccine campaigns have reduced the disease burden, much less progress has been made toward the control of HCV. Phylogenetic studies suggest that HCV originated in Africa and has been endemic in some regions for at least 500–600 years. However, little is known about the epidemiology, transmission, and clinical course of HCV in Africa. With the advent of highly effective anti-HCV agents, there exists great potential to at least curb the global epidemic. For regions such as sub-Saharan Africa, however, this will require a thorough understanding of the regional population-level epidemiology, risk factors, and transmission mechanisms. Only then can effective treatment and prevention strategies be introduced.